Is exposure to hydrocarbons associated with chronic kidney disease in young Nigerians? A case–control study - Okoye, Ogochukwu Chinedum; Awunor, Nyemike (Frontiers in Nephrology, 2022)
Introduction Although environmental exposure to hydrocarbons has been linked to non-communicable diseases, its association with chronic kidney disease (CKD) is still an emerging area. Epidemiological studies associating CKD with prolonged exposure to hydrocarbons have mostly focused on occupational exposure, with fewer studies on environmental exposure from residing in contaminated areas. The aim of this study was to determine any association between long-term exposure to petrochemical products and the risk of CKD by comparing the residence and occupational history of young patients with CKD and non-CKD controls. Materials and methods A case–control study of 74 cases and 74 age- and sex-matched non-CKD controls was carried out. Cases were patients with CKD who were aged 18–44 years and diagnosed with suspected chronic glomerulonephritis (CGN). Patients were recruited from an outpatient nephrology clinic and medical wards. Patients with CKD from traditional causes were excluded. Data were collected using a pre-tested structured questionnaire adapted from the WHO STEPwise approach to the non-communicable disease risk factor surveillance (STEPS) instrument. To assess exposure, a detailed work history and all residential addresses where the patients have lived for at least 5 years were recorded. ‘Exposed’ status was regarded as long-term residence in a known oil-polluted area and jobs involving crude oil exploration, processing, transportation and sales, and cleanup of crude oil hazards. Absence of a history of chronic exposure or any form of exposure was regarded as ‘less exposed’. Results There were 52 (70.3%) cases categorized as exposed, compared with 21 (28.4%) controls (p < 0.001). There were 34 (45.9%) cases born near petrochemical refineries and plants, compared with 11 (14.9%) controls (p ≤ 0.001). There were 34 (45.9%) cases residing near petrochemical refineries and plants, compared with 8 (10.9%) controls (p ≤ 0.001). When asked ‘Do you think you have been significantly exposed to crude oil?’, 15 (20.3%) cases and 2 (2.7%) controls answered ‘yes’ (p ≤ 0.001). Conclusion Our findings suggest an association between exposure to petrochemicals and CKD in young Nigerians diagnosed with suspected CGN. Exposure is significantly associated with a higher mean age, waist circumference, and blood sugar levels; however, other traditional risk factors for CKD were not considerably more prevalent in this unique patient population. These findings should prompt more emphasis on occupational history, residential history, and other relevant environmental exposures in the assessment of patients at risk for CKD.